PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA DI KELAS VI SD NEGERI 066050 MEDAN TAHUN PEMBELAJARAN 2018/2019 - Silaban, Patri Janson (Jurnal Ilmiah Aquinas, 2019)
This study aims to improve student learning outcomes by applying the inquiry learning model on Mathematics Debit lessons in class VI of Public Elementary School 066050 Medan Learning Year 2018/2019. This research is a Classroom Action Research (CAR). The research was conducted in two cycles. The subjects in this study were students of class VI SD Negeri 066050 Medan who collected 33 students consisting of 16 male students and 17 female students. Data obtained from research results from tests of student learning outcomes and observations. The learning model applied in this study is a learning model which is a design of activities designed by students involved in learning to think critically and analytically in finding their own answers to the problems in question through scientific experiments.The results of this study indicate an increase in student learning outcomes in Mathematics subject matter discharge with the application of inquiry learning models in class VI SD 066050 Medan. This can be seen from improving student learning outcomes every cycle. In class students who received complete grades as many as 6 students (18.18%) while 27 students (81.82%) got incomplete scores, with an average learning outcome of 43.94. In the posttest cycle I increased to 19 students (57.58%) completed while 14 students (42.42%) received incomplete scores, with an average value of 68.79 learning outcomes. In the posttest cycle II increased to 29 students (97.88%) completed while 4 students (12.12%) received incomplete scores, with an average value of learning outcomes 82.12.The observation results of teacher activities in the implementation of learning in the first cycle obtained a value of 60% with sufficient categories and in the second cycle the results of observation of teacher activities increased to 85.72% with a very high quality category. The results of observations on students in the learning process in the first cycle obtained a value of 57.14% with sufficient categories and in the second cycle the results of observations of student activities increased to 85.72% with a very good category.By looking at the results of learning outcomes and observations that can conclude the inquiry learning model there is an increase in learning outcomes of class VI students at SD Negeri 066050 Medan. Therefore the teacher continues to apply the inquiry learning model to improve student learning outcomes with Mathematics and other subjects.